Deficits of Tactile Passive Perception Acuity in Patients With Schizophrenia - Liu, Dan; Fan, Hong Zhen; Zhao, Wen Xuan; Wang, Yun Hui; Li, Dong; Wu, Jing Long; Yan, Tian Yi; Tan, Shu Ping (Frontiers in Psychiatry, 2020)
Background: Scarce literature has yet to characterize the tactile discrimination capability as well as the underlying mechanism of tactile deficits in psychotic disorder. In particular, very little is known regarding the tactile perception acuity in schizophrenia. Methods: A total of 131 clinically stable patients with schizophrenia (SCZ) and 79 healthy control (HC) volunteers were enrolled in the study. All the participants were tested on a tactile stimulus device which could quantify the tactile discrimination capability with right index finger scanned over the angles via the passive finger-movement apparatus. The MATRICS Consensus Cognitive Battery (MCCB) was adapted to assess the neurocognition of the participants. Correlation analysis and multivariate linear regression analysis were performed to investigate the relationship between tactile perception performance and neurocognitive function. Results: It was discovered that there existed a significant deficits in the tactile passive perception acuity (i.e., tactile angle discrimination threshold) in patients with schizophrenia compared with their healthy controls (F (3, 206) = 11.458, P = 0.001,partial η2 = 0.053). The MCCB total score and its six domains were significantly lower in SCZ patients than those in HCs (all p < 0.001). In the SCZ group, the composite score of the MCCB (r = −0.312, P < 0.001) and domains of neurocognition including speed of processing (r = −0.191, P = 0.031), attention/vigilance (r = −0.177, P = 0.047), working memory (r = −0.316, P < 0.001), verbal learning (r = − 0.332, P < 0.001), visual learning (r = −0.260, P = 0.004), and reasoning and problem solving (r = −0.209, P = 0.018) showed significant negative correlations with the tactile angle discrimination threshold. Multivariate linear regression analysis revealed that neurocognition impairment, especially the decline of working memory (B = −0.312, P < 0.001),underpin the tactile perception discrimination deficits in patients with SCZ. Conclusion: To the best of our knowledge, this is the first study to unravel the deficits of tactile passive perception acuity and its underlying neurocognition basis in patients with SCZ. This finding adds novel evidence to the subtle variation in haptic discrimination skills in schizophrenia which contributes to a more comprehensive understanding of the sensory profiles of this disorder.